Hubungan Penerimaan Diri dengan Kualitas Hidup Pasien Hipertensi - Susilawati, Ela; Cerli, Gita; Sabarguna, Boy Subirosa; Febriyanti, Hana (LPPM Universitas Respati Indonesia, 2025)
Background: Hypertension remains a major global health problem with a steadily increasing prevalence. More than one billion adults are reported to suffer from hypertension worldwide, while in Indonesia the prevalence reaches 34.1% among individuals aged over 18 years. This condition not only causes physical complications but also has psychological and social consequences. From a psychosocial perspective, hypertensive patients are at risk of experiencing anxiety, emotional distress, and difficulties in accepting their health condition. Low self-acceptance often generates negative emotions that can reduce quality of life. In Banten Province, hypertension prevalence was reported at 29.47%, with South Tangerang City recording the highest number of cases. However, most studies have focused on biomedical aspects, while the psychosocial dimension, particularly the role of self-acceptance in determining quality of life, has been rarely explored. Methods: This study employed a cross-sectional design using purposive sampling involving 100 hypertensive patients at Rawa Buntu Primary Health Center, South Tangerang City. The research instruments included the Acceptance of Illness Scale (AIS) and the Mini-Questionnaire of Quality of Life in Hypertension (MINICHAL). Data analysis was performed using the chi-square test. Results: showed that 95% of respondents reported high self-acceptance and 5% low; meanwhile, 93% had good quality of life and 7% poor. Statistical testing confirmed a significant association between self-acceptance and quality of life (p < 0.001). Conclusion: self-acceptance plays a crucial role in improving quality of life among hypertensive patients. Psychosocial support and health counseling are clinically recommended to help patients adapt to their condition and maintain well-being.